Artificial Intelligence in Financial Reports: How it Affects the Process's Effectiveness and Efficiency - Kuswara, Zakaria; Pasaribu, Marsel; Fitriana, Fitriana; Santoso, Rachmat Agus (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
In today's digital age, artificial intelligence (AI) has revolutionized many sectors, including auditing and finance, with the potential to improve the efficiency and effectiveness of the audit process. However, there is limited understanding of the impact of AI implementation on financial statement transparency and external auditor reputation. This study aims to fill that knowledge gap by exploring how AI can strengthen financial statement transparency and enhance auditor reputation. The methodology used is descriptive-analytical with an empirical normative approach, collecting data through literature review and documentation. The results finds that the integration of AI in auditing significantly improves financial statement transparency, facilitates auditors in conducting more in-depth and accurate analyses, and potentially enhances the reputation of external auditors in the eyes of stakeholders. The findings confirm that AI not only improves the efficiency of the audit process but also plays a strategic role in building trust and integrity in financial reporting. The implications of this research are significant in demonstrating the importance of adapting the latest technologies to meet and exceed evolving financial and reputational expectations in the digital age.